Comparison of trauma outcomes between Japan and the USA using national trauma registries. Issue 1 (5th November 2018) - Matsumoto, Shokei; Jung, Kyoungwon; Smith, Alan; Yamazaki, Motoyasu; Kitano, Mitsuhide; Coimbra, Raul
Abstract : Background: The National Trauma Data Bank (NTDB) has served as a global benchmark for trauma care quality and outcomes. Herein, we compared patient characteristics, trauma management, and outcomes between Japanese emergency and critical care centers and US level 1 trauma centers using the Japanese Trauma Data Bank (JTDB) and NTDB. Methods: A retrospective cohort matching (1:1) study was performed. Patients treated in 2013 with an Injury Severity Score ≥9 were included. The primary outcome measure was in-hospital mortality. The secondary outcome measures included the hospital length of stay and the rate of use of radiological diagnostic modalities. Results: A total of 14 960 pairs with well-balanced characteristics were generated from 22 535 and 112 060 eligible patients in the JTDB and NTDB, respectively. Before matching, the in-hospital mortality was higher in the JTDB than in the NTDB (7.6% vs. 6.1%; OR, 1.28; 95% CI 1.21 to 1.35). However, after matching, the in-hospital mortality was lower in the JTDB cohort (4.2% vs. 5.8%; OR, 0.72; 95% CI 0.65 to 0.80). CT scans were used in >80% of JTDB patients, which was more than 1.5 times as often as the use in the NTDB cohort. In subgroup analyses, only patients who received a blood transfusion had a poorer survival outcome in the JTDB compared with the NTDB (OR, 1.32; 95% CI 1.07 to 1.64). Discussion: We observed marked differences in trauma care between Japan and the USA. Although the quality of the recent Japanese trauma care appears to be approaching that of the USA, it may be further improved, such as by the establishment of transfusion protocols. Level of evidence: Level IV.